Preparation of activated charcoal from Acrocomia aculeata for purification of pretreated crude glycerol - Barbosa, Sandro L.; de Freitas, Milton S.; dos Santos, Wallans T. P.; Nelson, David Lee; de Freitas Marques, Maria Betânia; Klein, Stanlei I. [UNESP]; Clososki, Giuliano C.; Caires, Franco J.; Nassar, Eduardo J.; Zanatta, Lucas D.; Agblevor, Foster A.; Afonso, Carlos A. M.; et al. (Springer Nature, 2020)
Activated charcoal was prepared from Acrocomia aculeata (macaúba) endocarp by ZnCl2 activation and then used for the adsorptive purification of pretreated crude glycerol (CG) containing pigments, such as β-carotene. The pretreatment of glycerol involved filtration of the K3PO4 formed by the addition of H3PO4 to the crude glycerol containing KOH. A mixture of 1.38:1 w/w of ZnCl2:Acrocomia aculeata pulp was heated at 120 °C with stirring for 24 h. The mixture was activated by heating at 600 °C for 3 h. The activated charcoal was cooled to 25 °C, washed with a 1:1 mixture of methanol and water (100 mL) and heated at 150 °C for 2 h. The surface properties of the activated charcoal (surface area 627 m2 g−1, pore volume 0.39 m3 g−1, Bronsted sites 118.23 μmol g−1, and Lewis sites 104.86 μmol g−1) and the adsorption capacity for impurities in H3PO4-pretreated crude glycerol were investigated. The activated charcoal exhibited the most suitable surface properties for the purification of pretreated crude glycerol, attaining a 95.99% glycerol concentration (by GC) using 10 g/L with gravity filtration through a column at room temperature over a 48-h period. The purified glycerol was characterized by GC/MS, 1H- and 13C-NMR, and DSC and TG analyses. The activated charcoal was regenerated by washing with methanol and hexane and heating to 150 °C for 5 h. The activated charcoal could be re-used three times to remove all of the pigments before it was necessary to re-activate the charcoal by heating with ZnCl2.
Keywords: Endocarp pulp of Acrocomia aculeata; Microporous-mesoporous charcoal; Prepared charcoal; Purification of crude glycerol by adsorption